A taxonomic revision and phylogenetic reconstruction of the Jahnulales (Dothideomycetes), and the new family Manglicolaceae - Suetrong, S.; Boonyuen, N.; Pang, Ka-Lai; Ueapattanakit, J.; Klaysuban, A.; Sri-indrasutdhi, V.; Sivichai, S.; Jones, E.B.G. (2011)
Genera assigned to the Jahnulales are morphologically diverse, especially in ascospores equipped with or without appendages, sheaths or apical caps. They are predominantly freshwater fungi occurring on woody substrata, with Manglicola guatemalensis, Xylomyces chlamydosporus and X. rhizophorae the only species known from marine habitats. The order Jahnulales with 4 teleomorphic genera: Jahnula (15 species), Aliquandostipite (5), Megalohypha (1), Manglicola (2) and the anamorphic genera Brachiosphaera (2), Speiropsis (9), Xylomyces (8), amounting to a total of 42 species, is reviewed and nomenclatural changes are proposed. Twenty species are treated at the molecular level, with 94 sequences, 13 of which are newly generated for this review. Three species are rejected (Speiropsis irregularis, Xylomyces aquaticus, X. elegans) while the phylogenetic placement of 6 Xylomyces, 7 Speiropsis, 1 Brachiosphaera and 1 Manglicola require molecular data to confirm their placement in the order. Sequences are derived from ex-holotype isolates and new collections made in Thailand. Most taxa are included in the family Aliquandostipitaceae and a new family Manglicolaceae is erected for the marine ascomycete Manglicola guatemalensis with its large ascomata (1,100-1,750 x 290-640 mu m), wide ostioles and ascospores that are fusiform, unequally one-septate with the apical cell larger than the turbinate basal cell and bear apical gelatinous appendages. The genus Jahnula is polyphyletic grouping in three clades with J. aquatica, J. granulosa, J. rostrata, J. potamophila and Megalohypha aqua-dulces in the Jahnula sensu stricto clade. No taxonomical changes are proposed for Jahnula species not grouping in the Jahnula sensu stricto clade, until further species are isolated and sequenced.